"Restorative Justice" or Restoring Order? Restorative School Discipline Practices in Urban Public Schools. (October 2021) - Lustick, Hilary
Suspension rates for students of color are higher than for White students, even in schools that utilize alternatives to suspension like restorative practices. This study draws on data from a year-long multicase ethnography that sought to elucidate why such disproportionality prevails in schools that use restorative practices. This article focuses on one finding: that the individuals hired to be restorative coordinators were consistently young, non-White staff from the same neighborhoods as their students. The majority-White faculty and administration greatly depended on these coordinators to bond with, contain, and compel obedience from students of color.